H2sensing response of flame-spray-made Ru/SnO2thick films fabricated from spin-coated nanoparticles - Chaikarn Liewhiran (2018)
High specific surface area (SSABET: 141.6 m2/g) SnO2nanoparticles doped with 0.2-3 wt% Ru were successfully produced in a single step by flame spray pyrolysis (FSP). The phase and crystallite size were analyzed by XRD. The specific surface area (SSABET) of the nanoparticles was measured by nitrogen adsorption (BET analysis). As the Ru concentration increased, the SSABETwas found to linearly decrease, while the average BET-equivalent particle diameter (dBET) increased. FSP yielded small Ru particles attached to the surface of the supporting SnO2nanoparticles, indicating a high SSABET. The morphology and accurate size of the primary particles were further investigated by TEM. The crystallite sizes of the spherical, hexagonal, and rectangular SnO2particles were in the range of 3-10 nm. SnO2nanorods were found to range from 3-5 nm in width and 5-20 nm in length. Sensing films were prepared by the spin coating technique. The gas sensing of H2(500-10,000 ppm) was studied at the operating temperatures ranging from 200-350 °C in presence of dry air. After the sensing tests, the morphology and the cross-section of sensing film were analyzed by SEM and EDS analyses. The 0.2%Ru-dispersed on SnO2sensing film showed the highest sensitivity and a very fast response time (6 s) compared to a pure SnO2sensing film, with a highest H2concentration of 1 vol% at 350 °C and a low H2detection limit of 500 ppm at 200 °C. © 2009 by the authors.